Endobronchial Lipoma Causing Almost Completely Trachea Obstruction - Gaoyan He; Jie Zhao; Xiaojuan Wu; Bo Li; Xiaobin Luo; Tao Zhu (Respirology Case Reports)
ABSTRACT Even though endobronchial lipoma is rare, it can mimic malignancy and lead to significant complications such as progressive dyspnea and subsequent lung infections related to endobronchial obstruction. We present a case of endobronchial lipoma located in the trachea causing almost complete tracheal obstruction. The patient's dyspnea disappeared after undergoing bronchoscopic excision of the mass.